Doing Business in Kazakhstan 2017 - World Bank (Washington, DC, 2017)
Doing Business in Kazakhstan 2017 is the first report of the subnational Doing Business series in Kazakhstan. It measures business regulations and their enforcement in four Doing Business areas. The objective of the study is to gain a broader understanding of the business regulatory environment across Kazakhstan as well as to provide good-practice examples and reform recommendations to help guide policy at the national and subnational levels. The study focuses on indicator sets that measure the complexity and cost of regulatory processes affecting four stages in the life of a small to medium-size domestic firm—starting a business, dealing with construction permits, getting electricity and registering property. These four indicator sets were selected because they relate to areas of business regulation where implementation of the common legal and regulatory framework differs across locations. While highly centralized line ministries hold the direct formal authority for the delivery of most services across the territory, regions as well as Almaty city and Astana wield local power and authority, especially in the areas of getting electricity and dealing with construction permits. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why.